Volumetric modulated arc therapy versus 3D conformal radiotherapy for selected childhood neoplasms. Issue 1 (21st November 2014) - Chojnacka, Marzanna; Zygmuntowicz-Piętka, Anna; Semaniak, Anna; Pędziwiatr, Katarzyna; Dąbrowski, Ryszard; Skowrońska-Gardas, Anna
Abstract Aim The comparative study of the plan quality between volumetric modulated arc therapy (VMAT) and 3D conformal therapy (3DCRT) for the treatment of selected representative childhood neoplasms was performed. Materials and methods During the year 2013, 44 children with neoplasms were irradiated using VMAT. The 3DCRT plans were created retrospectively and compared with the VMAT plans for four tumour locations. The conformity parameters, dose volume histograms for target volume and organs at risk, number of monitor units and time used to deliver the single fraction were evaluated and compared for each plan. Additionally, for patients with brain tumour the comparison of different arcs configuration was made. Results VMAT modality presented the superiority over older conformal methods with regard to the improvement in the dose conformity and normal tissue sparing. The noncoplanar arcs arrangement was beneficial in the decrease of high-dose volume and the protection of the organs at risk located oppositely to the target volume. Findings VMAT could be preferred technique for treating childhood neoplasms, especially when the complex-shaped target volume is localised close to the critical structures. The noncoplanar arcs arrangement could be the method of choice in the reirradiated patients and in these with laterally located brain tumours.